DNA and PNA as templates for building nanoassemblies via electrostatic complexation with gold nanoparticles - Gourishankar, A; Shukla, S; Pasricha, R; Sastry, M; Ganesh, Krishna N. (Current Applied Physics, 2005)
Organisation of nanoparticles on structurally well-defined templates is a first step towards creating nanomachines. In this respect, nucleic acids are ideal structural templates and a variety of secondary structures realizable from DNA/RNA - e.g., duplexes, hairpins, triplexes, cruciforms, tetraplexes can be exploited to engineer nanoparticle organization at will. We have used oligonucleotides and their analogues such as phosphorothioates and peptide nucleic acids to electrostatically encapsulate cationic-capped gold nanoparticles. This article describes synthesis and characterization of DNA/PNA-gold nanoparticle composites using TEM and UV-T-m techniques. These types of assemblies may have potential for creating nanowires and lithographic circuits. (C) 2004 Elsevier B.V. All rights reserved.
Indo-Japan Workshop on Advanced Molecular Electronics and Bionics, Kyushu Inst Technol, Grad Sch Life Sci & Syst Engn, Kitakyushu, JAPAN, DEC 11-13, 2003
Keywords: DNA; DNA-gold nanoparticle interactions; nanoassemblies; PNA